The Effect of Strategic Leadership and Positive Learning Climate on Teacher Teaching Performance - Dian Megawati; Sururi Sururi; Yayah Rahyasih (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
This study investigates how strategic leadership and a positive learning climate influence teachers' instructional performance in Indonesian primary schools, addressing ongoing challenges in improving teaching quality within resource-constrained contexts. Using a quantitative survey of 300 teachers from 51 public schools in Purwakarta Regency, West Java Province, the data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings demonstrate that strategic leadership exerts significantly stronger influence (β=0.527, f²=0.453) on instructional performance compared to positive learning climate (β=0.295, f²=0.142), with strategic leadership producing 1.79 times greater effect. Together, both variables explain 49.4% of the variance in teachers' instructional performance, with strategic leadership accounting for the preponderance of this explanatory power. The study concludes that enhancing strategic leadership particularly through developing vision, coordinating programs, supervising instruction, monitoring progress, and ensuring accountability constitutes the primary lever for improving teaching effectiveness in resource-limited Indonesian schools. These evidence-based findings provide crucial guidance for policymakers and school leaders to strategically allocate limited professional development resources, prioritizing high-leverage leadership practices that maximize returns on investment. Implications address national policy reforms for principal preparation, district-level coaching programs, and school-level implementation of systematic supervisory practices.